Peter Howson and the Language of Salvation: The Role of the Grotesque in Redemption's Hades Cycle - Froehlich, Caleb (Religion and the arts, 2019)
Since his conversion to Christianity in 2001, Peter Howson's religious paintings have generally been met with critical incomprehension. A case in point was his 2012 exhibition Redemption, where reviewers suggested an irreconcilable incongruity between its grotesque imagery and redemption, the exhibition's title. In response to this critical bewilderment, the present article argues for the appropriateness of the grotesque in Howson's depictions of salvation by examining the significance of his conversion experience and providing a more sophisticated and developed analysis of the grotesque as his visual language. More specifically, it utilizes insights from an analysis of the content and practice of the artist's belief system and a new taxonomy of the grotesque in a close reading of the Hades cycle, featured in Howson's Redemption exhibition, in order to show how the artist communicates salvation through the grotesque. It is hoped that this article may serve as useful groundwork for other scholars engaging with Howson's extraordinary religious art.